Social networks privacy policy awareness among undergraduate students: the case of Twitter - Talib, Shuhaili; Ismail, Nur Ain; Olowolayemo, Akeem Koye; Syed Naser, Sharifah Aina; Haron, Siti Zalifah; Mohammad Yusof, Asma Hanisah (IEEE, 2014)
People nowadays freely give out their personal information on social media without knowing the implications of such actions. The proliferation of social networking sites creates the illusion of fun that made people to overlook the downsides of using these media. This paper examines the privacy awareness and general concerns of undergraduate students who form the bulk of users of these media. An evaluation of students has been carried out to assess their level of concern for privacy and how conscientious they are regarding privacy policies. The work also examines whether based on the awareness, users are more careful or generally carefree. Furthermore, the research also sought to evaluate whether the privacy policies as currently presented is adequate. Another objective of the research is to examine better ways of engaging users if the composition and presentation of privacy policies are found to be contributive to the low level engagement.